Development of poultry production sustainability through bio-digestors - Souza, Sulma Vanessa; Gimenes, Régio Marcio Toesca; Orrico, Ana Carolina Amorim; De Almeida, Marcel Goncalves; Sabbag, Omar Jorge [UNESP] (Centro Universitario de Maringa, 2022)
The economic viability of a bio-digestor in a broiler production unit is analyzed. Chicken coup bedding with rice bran and shavings is employed as the substrate for the generation of energy, aiming at the production of clean and renewable energy in the form of biogas and retrieval of biofertilizers. It is a sustainable model for the treatment of wastes generated by the poultry industry. Research comprised a case study through a half-structured interview. Current techniques were employed as a criterion for the evaluation of the project's economical viability: Net present price (NPP), Return internal rate (RIR), Profit index (PI), Relationship Costs Benefits (B/C), Internal rate of modified return (IRMR), Uniform Annual equivalent value (UAEV) and payback discount (PBd) by determining the minimum attractivity rate (MAR) of 9.57% per year. Results of viability analysis showed the following rates: NPP=R$ 178,304.15; RIR=13.17%; PI=1.22; B/C=3.36; IRMR=10.81%; UAEV=R$ 22,869.86; PBd=10.65 years for biogas produced from chicken coup bedding with rice bran. In the case of shavings, the following results were obtained: NPP=R$ 147,007.60; RIR=12.55%; PI=1.18; B/C=2.36; IRMR=10.81%; UAEV=R$ 18,855.67; PBd=11.57 years. Both projects were positive, although the generation of biogas from chicken coup bedding with rice bran was the better option.
Desenvolvimento da sustentabilidade avícola a partir do uso de biodigestores
Keywords: Biogas; Chicken coup bedding; Economic viability; Production of chickens